Pain Management after Laparoscopic Cholecystectomy by Intraperitoneal Bupivacaine - Tayyaba Jaffri, Syed Shehzad Hussnain, Kanwal Hyder, Fahad Gul, Farooq Sultan Minhas, Saadia Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the effectiveness of 0.5% bupivacaine spray on the gallbladder at the end of surgery with the effectiveness of no spray in reducing postoperative pain within the first 24 hours. Study design: Randomized Controlled Trial Place and duration: The study was conducted in the Department of General Surge,Combined Military Hospital, Rawalpindi, from 23 July 2018 to 22 January 2019, after receiving approval from the ethics review board. Method: A total of 62 patients underwent laparoscopiccholecystectomy. Indications were symptomatic gallstones (such as dyspepsia, pain in right hypochondrium, and pain after eating fatty meals). The patient age group was between 20-60 years. Patients includedAcutecholecystitis, choledocholithiasis, pancreatitis and bile leakage during surgery. However pregnant females and patients with co-morbidities were not included. Informed consent was taken from all the patients.At the end of the laparoscopic cholecystectomy, Group A infused 0.5% bupivacaine into the gallbladder depression at a standard weight of 2mg/kg, but Group B did not receive a local anaesthetic. Postoperative pain was assessed and scored in both groups from 0 to 10 at 6 and 24 hours using the VAS (Visual Analogue Scale). Result: The mean age of patients in group A was 38.23±8.13 years, and in group B, 38.74±6.64 years. Most of the 35 patients (56.54%) were between 20 and 40 years of age. Among 62 patients, 35(56.54%) were male and 47(75.81%) were female. So the male-to-female ratio is 1:3.2. Efficacy (0.5% bupivacaine) was 22 patients (70.97%) in group A (intervention group) and 11 patients (35.48%) in group B (control group) (p-value = 0.005). Conclusion: The study resulted that the effectiveness of 0.5% bupivacaine spray on the gallbladder at the end of surgery was superior to that of the control group. Keywords: Bupivacaine Spray, LaparoscopicCholecystectomy, Postoperative Pain, VAS (Visual Analogue Scale).